Children's literature review. - Krstovic, Jelena O. (Gale virtual reference library., 2012)
Presents full-text literary criticism on writers and illustrators for children and young adults. Critical essays are selected from leading sources, including published journals, magazines, books, monographs, reviews, and scholarly papers.